Anchoring porous F-TiO2 particles by directed-assembly on PMIA separators for enhancing safety and electrochemical performances of Li-ion batteries. (1st March 2023) - Hu, Xue; Li, Yinhui; Chen, Zan; Duan, Cuijia; Yuan, Biao
Abstract: The safety of lithium-ion batteries (LIBs) has always been a research hotspot in the field of new energy. Herein, F-TiO2 /PMIA composite separator with thermotolerance and mechanical robustness is designed and fabricated by directed-assembly with strong hydrogen bonding between the poly (m-phenylene isophthalamide) (PMIA) and fluorine functionalized porous titanium dioxide (F-TiO2 ). The results show that F-TiO2 /PMIA composite separator exhibits excellent mechanical properties with tensile strength of 24.6 MPa. The elongation at break is 45.6%, which is increased by 591% compared with PMIA separator (6.6%), closing to Celgard PP separator (48.5%). At the same time, the F-TiO2 /PMIA composite separator possesses flame resistance and self-extinguishing properties. Moreover, does not shrinkage under the heating conditions of 250 °C, which greatly improves the safety of LIBs. In terms of electrochemical performance, F-TiO2 /PMIA composite separator has the highest ionic conductivity (1.30 mS cm −1 ) and delivers a high initial discharge capacity of 146.6 mAh g − 1 and a discharge capacity of 134.3 mAh g − 1 after 50 cycles at 0.2 C, with capacity of 90.1 mAh g − 1 at 2 C. Therefore, the novel F-TiO2 /PMIA composite separator offers promising commercial prospects in future high-safety and high-performance energy applications.